Burmese (Myanmar) : an introduction to the spoken language. - Okell, John; Saw Tun, U; Khin Mya Swe, Daw (Northern Illinois University Press, 2010)
The second volume in a four-part language course, this textbook builds on the spoken language lessons from Book 1 and contains more advanced speaking exercises and practice dialogs, as well as activities to reinforce the material presented in Book 1. The material of Book 2 is arranged in five levels, each of which covers the same set of topics, but each succeeding level both consolidates and extends the learnerÆs proficiency in the topic. The lessons are followed by appendices on etiquette and social behavior in Burma and an outline of Burmese grammar. Okell also presents more extensive vocabulary lists, both Burmese-English and English-Burmese, which are arranged by topic and include such categories as names of clothes, foods, and talking with Buddhist monks. Like the other titles in this series, Book 2 is accompanied by audio files and can be used either under the instruction of a teacher or for self-study. The series was developed over a period of several years and was tested, modified, and expanded after use in the classroom. Language professors and their students or those learning Burmese on their own will appreciate the accessible approach and the manageable size of the lessons of the very practical textbooks in this series.